The Influence of Work Behavior and Competence on Performance Through Job Satisfaction in Permanent Education Workers Non Pns Faculty of Engineering Brawijaya University Malang - Ratna Sri HARTATIK; Ernani HADIYATI; Gunadi GUNADI (Indonesia Strategic Sustainability, 2023)
Implementing higher education for tertiary institutions involves all existing elements to achieve the quality of higher education internal services. One of the essential components in the management of the tertiary education system is the academic community, which has a scientific tradition and academic culture. The academic community in a tertiary institution consists of teaching staff (lecturers), students, education staff and stakeholders, where each has different main tasks and functions to improve the quality of tertiary services. This study aims to examine and analyze the influence of work behavior, competence and job satisfaction on the performance of non-civil servant (non-PNS) permanent education staff at the Faculty of Engineering, University of Brawijaya Malang. This study uses qualitative data types from primary data, namely, 70 employees as respondents. The data analysis method used in this study is Partial Least Squares (PLS) with a new Structural Equation Modeling (SEM) approach, which can predict the relationship between the dependent and independent variables. The results of this study provide information that there is a positive and significant influence between behavior and competence on performance. This study also provides information that there is a positive and significant influence between behavior and competence on job satisfaction. In addition, the job satisfaction of non-PNS permanent staff of FT UB Malang has a positive and significant effect on performance as well as a positive and significant effect on work behavior and competence of non-PNS permanent education staff on performance through job satisfaction.